Ingestive Behavior of Dairy Cattle in Two Contrasting Tropical Production Systems in Colombia - Montoya, S.; García, M. P.; Orozco, A. M.; Suarez, J. F.; Escobar, C. S.; Tapie, W. A. (Faculty of Animal Science, IPB University, 2026)
In dairy cattle, ingestive behavior is influenced by environmental, nutritional, and management factors. The objective of the study was to describe the ingestive behavior and productive performance of dairy cows in two contrasting dairy production systems in Colombia: a lowland system at 941 m above sea level (a.s.l.) with Lucerna cows, and a highland system at 2500 m a.s.l. with Holstein cows. The temperature-humidity index (THI), forage and water intake, as well as behavioral patterns, were monitored under each system. In the lowland system, the THI values exceeded 85 during afternoon hours, reaching emergency levels; however, Lucerna cows exhibited no clinical signs of heat stress, suggesting thermal resilience. In the highland region, THI remained within the alert range (72-79). Dry matter intake (DMI) as a percentage of body weight was 2.42% in the lowland system and 1.68% in the highland system. Feed efficiency was lower in the lowland system (69.56%) than in the highland system (96.67%). Milk yield per unit of metabolic body weight (BW0.75) was 0.119 kg/kg BW0.75 in the lowland system and 0.206 kg/kg BW0.75 in the highland system. Water intake per 100 kg of body weight was 13.31 L in the lowland system and 16.12 L in the highland system. Forage quality was superior in the highland system, with greater crude protein levels and lower fiber content. Both systems showed metabolizable energy deficits, which increased when accounting for energy expenditures associated with walking. These findings underscore the critical need to tailor management strategies to the unique environmental and nutritional conditions of each production system, thereby enhancing animal welfare and optimizing productivity.